Harmonization of Indonesia’s Tourism Policies in 2015 – 2018 - Havidz Prakoso (University of Muhammadiyah Malang, 2023)
Globalization integrates all state and non-state actors in domestic and international level; thus, interaction process among actors runs intensely and create independency through the improvement of policy integration that yields possitive correlation to sustainable development. Tourism becomes one of the issues and developmental programs that is designed as an encouragement of nation economic growth through some values integrated in global policy and contributions from various affiliations called multiplier industry in which the government provides the primary field. Under the leadership of president Joko Widodo, Indonesia also expects to obtain the possitive impacts of tourism sector growth through designing a set of policy prepared to boost sustainable economic growth in which its implementation is carried out under the supevision of the Minister of Tourism, Arief Yahya. The present research utilized Learning theory that performed capillary process by means of policy adjustment as Intermestic study and Tourism-related policies and programs as the process of international policy harmony – global values used as a framework of the happening phenomena. Further, the data were analyzed qualitatively by employing literature reviews. The result of the analysis showed there were policy harmonization and integration in most sectors especially in Tourism where the ministry of tourism has authority to manage and adjust to the higher level of policy (global) through the adaptation to the policy established by UNWTO.